2004
DOI: 10.1063/1.1787159
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube alignment by surface acoustic waves

Abstract: We present a realization of carbon nanotube alignment. Surface acoustic waves are applied to a multiwalled carbon nanotube suspension and the lateral piezoelectric field of the standing wave aligns the carbon nanotubes with an angle of 25° to 45° on LiNbO3 with respect to the direction of wave propagation. This angle results from a superposition of the aligning electric field and a perpendicular fluidic flux in the carbon nanotube suspension caused by the energy transfer from the surface acoustic wave into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 15 publications
2
80
0
Order By: Relevance
“…In their method, thiol end groups were produced chemically on the SWNT ends and defects, and then by surface acoustic waves to a SWNT suspension, the SWNT were oriented with respect to the electrodes. [44] Thus, the AuNPs were tethered to the thiolated SWNTs. The SWNTs and AuNPs were characterized by SEM images.…”
Section: Preparation Of Aunp-filled Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their method, thiol end groups were produced chemically on the SWNT ends and defects, and then by surface acoustic waves to a SWNT suspension, the SWNT were oriented with respect to the electrodes. [44] Thus, the AuNPs were tethered to the thiolated SWNTs. The SWNTs and AuNPs were characterized by SEM images.…”
Section: Preparation Of Aunp-filled Cntsmentioning
confidence: 99%
“…[60] The driving force for the self-assembly was the formation of a surface-combined pseudorotaxane (Scheme 3). The stable dispersion of dodecanethiol-modified AuNPs was prepared by the method described by Brust et al [44] The nearly size-monodisperse fraction was subsequently modified by the exchange of the adsorbed thiol for thiol-incorporating crown molecules (dodecanethiol incorporating a crown moiety in the terminal position). [61] The MWNTs were modified by two amide-coupling reactions: the first was between the carboxy-modified MWNTs and ethylenediamine, and the second between the remaining amine of the coupled ethylenediamine and the cation precursor [N-(4-carboxydibenzylamine)carbamate].…”
Section: Preparation Of Aunp-filled Cntsmentioning
confidence: 99%
“…[19][20][21] Forces and flows induced in a fluid by SAWs separate cells, [22][23][24] align nanowires, and deagglomerate nanotubes. [25][26][27][28][29] The comprehensive discussion of results obtained in the field of acoustomicrofluidics as well as extensive lists of references can be found in review publications. [30][31][32][33][34][35][36] Theoretical considerations of SAW-driven effects are also the focus of researchers' attention.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It was found that the velocity of propagation of the domain walls depends on the amplitude of the SAW. In the area of microfluidics, recent research demonstrates that SAWs provide an effective means to manipulate fluids (fluid mixing, [13][14][15] translation, [16][17][18] jetting, 19 and atomization 20 ) and manipulate particles (handling, 21 focusing, 22 separation, 23,24 sorting, 25,26 concentration, [27][28][29][30] and reorientation 31 ) in lab-on-a-chip devices for applications in chemistry, biology, and medicine. The ability for a SAW to mix, translate, jet, and atomize droplets is dictated by its amplitude.…”
mentioning
confidence: 99%